Pendampingan Pelaksanaan Pembelajaran Melalui Kegiatan Kampus Mengajar di SDN 45 Gresik - Farah Nabilah Hanin,; Mahardhani, Ardhana Januar (TAAWUN, 2022)
Kampus Mengajar is a program of the Merdeka Belajar-Kampus Merdeka held by the Ministry of Education and Culture of the Republic of Indonesia. Activities in the Kampus Mengajar provide opportunities for students to knowledge insight and gain experience in helping the teaching and learning process in elementary schools. This activity was carried out for five months with the method of mentoring and training activities. Assistance is carried out through teaching and learning activities, adapting technology, developing literacy and numeracy skills for students, as well as activities for teachers at SDN 45 Gresik in the form of developing online-based learning materials.